Meaning, subjectivity, society : making sense of modernity - Smith, Karl E. (International comparative social studies ;, 2010)
"This book grapples with questions at the core of philosophy and social theory - who am I? Who are we? How are we to live? That is, questions of what humans are capable of, the 'nature' of our relationships to each other and to the world around us, and how we should live. They appear to be both prohibitive and seductive - that they are ultimately irresolvable makes it tempting to leave them alone, yet we cannot do that either. This interdisciplinary investigation proceeds primarily as a dialogue with Cornelius Castoriadis and Charles Taylor."--Jacket